Partial pensions as a form of flexible retirement in the EU countries - Bielawska, Kamila (Emerytury częściowe jako instrumenty elastycznego przechodzenia na emeryturę w krajach Unii Europejskiej, 2017)
Demographic ageing will affect the EU economy, public finances and adequacy and sustainability of pension systems. A key response to the challenge of ageing population is the extension of working lives. This paper seeks an answer for the question if the partial pension may be an efficient solution to make people work longer. Comparative analysis of the partial retirement in selected EU countries gives no unquestionable conclusions in this question, especially in terms of hours worked. The results highly depend on the construction of the partial pensions and the changes on the labour market. Taking into account both the further pension reforms to make people work longer and simultaneously the pressure on the pension replacement rates, the idea of the partial pension seems to be attractive and worth further research
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 9-18
Keywords: employment; partial pension; effective retirement age; zatrudnienie; emerytura częściowa; efektywny wiek emerytalny